The Influence of Gratitude on Happiness from the Perspective of Islamic Psychology: A Literature Review - Iqbal, Muhammad (Riwayat: Educational Journal of History and Humanities, 2025)
Human life will never be separated from the aspect of psychological happiness. Every individual tries to create a happy existence, including physical, social and mental conditions, so that the quality of life can improve. One of the factors that influences happiness is gratitude. This is because gratitude can produce a positive perspective on all events that occur in daily life. The aim of this literature review is to analyze literature related to the influence of gratitude on happiness from an Islamic psychology perspective. The databases used are Scholar, PubMed, Science Direct, Semantic Scholar, Researchgate. The keywords used are Gratitude, Grateful, Happiness, excitement, Islam. The results of the literature search obtained 6 articles. Search results go through a filtering process with PICO elements and the CRAAP method. The research results show that gratitude has an important role in increasing happiness according to an Islamic psychology perspective. Gratitude contributes positively to mental and spiritual well-being, especially in the context of Islamic education. For this reason, it is important to integrate the values of gratitude into Islamic education programs as a strategic action to improve a person's mental and spiritual well-being. Applying the principles of gratitude in daily activities can also strengthen the foundation of overall mental and spiritual health.